Camada negra - Borau, José Luis; Molina, Ángela 1955-; Ponte, Maria Luisa 1918-1996 (Divisa Home Video, 2016)
Tatin is a 14 year-old boy who admires his brothers and wants to be like them, a member of an ultra-Right group. But they all laugh at him and consider him too young. He meets Rosa, a girl who is a little older and who notices him, giving him some affection. But Tatin believes in complying with three conditions that he had one day heard a fanatic tell his mother and the third condition is directed against Rosa
Original: Spanien, 1977. - Sprache: spanisch
Keywords: Right-wing extremists / Spain / Drama; Teenage boys / Spain / Drama; Ethnic relations; Right-wing extremists; Teenage boys; Spain / Ethnic relations / Drama; Spain; Spanien; DVD-Video